A Donation After Circulatory Death Program Has the Potential to Increase the Number of Donors After Brain Death*. Issue 2 (February 2016) - Broderick, Andrew R.; Manara, Alex; Bramhall, Simon; Cartmill, Maria; Gardiner, Dale; Neuberger, James
Abstract : Objectives: Donation after circulatory death has been responsible for 75% of the increase in the numbers of deceased organ donors in the United Kingdom. There has been concern that the success of the donation after circulatory death program has been at the expense of donation after brain death. The objective of the study was to ascertain the impact of the donation after circulatory death program on donation after brain death in the United Kingdom. Design: Retrospective cohort study. Setting: A national organ procurement organization. Patients: Patients referred and assessed as donation after circulatory death donors in the United Kingdom between October and December 2013. Interventions: None. Measurements and Main Results: A total of 257 patients were assessed for donation after circulatory death. Of these, 193 were eligible donors. Three patients were deemed medically unsuitable following surgical inspection, 56 patients did not proceed due to asystole, and 134 proceeded to donation. Four donors had insufficient data available for analysis. Therefore, 186 cases were analyzed in total. Organ donation would not have been possible in 79 of the 130 actual donors if donation after circulatory death was not available. Thirty-six donation after circulatory death donors (28% of actual donors) were judged to have the potential to progress to brain death if withdrawal of life-sustaining treatment had been delayed by up to a further 36 hours. A further 15 donation after circulatory death donors had brain death confirmed or had clinical indications of brain death with clear mitigating circumstances in all but three cases. We determined that the maximum potential donation after brain death to donation after circulatory death substitution rate observed was 8%; however due to mitigating circumstances, only three patients (2%) could have undergone brain death testing. Conclusions: The development of a national donation after circulatory death program has had minimal impact on the number of donation after brain death donors. The number of donation after brain death donors could increase with changes in end-of-life care practices to allow the evolution of brain death and increasing the availability of ancillary testing.